Impact of emotional intelligence on adherence to the Mediterranean diet in elementary education school students. A structural equation model - Eduardo Melguizo-Ibáñez; Georgian Badicu; Filipe Manuel Clemente; Ana Filipa Silva; Jose Luis Ubago-Jiménez; Gabriel González-Valero (PeerJ, 2022)
Background Adolescence is one of the stages where a large number of physical, psychological and emotional changes occur, the latter playing a key role in adherence to a healthy dietary pattern. Taking into account the above, this research reflects the objectives of developing an explanatory model of the incidence of attention, clarity and emotional repair on adherence to the Mediterranean diet and to contrast the structural model through a multigroup analysis based on Mediterranean adherence to this dietary pattern. Methods To this end, a comparative descriptive cross-sectional study has been carried out with 293 students from the third cycle of primary education. The instruments used were a sociodemographic questionnaire, the KIDMED test and the Trait Meta-Mood Scale (TMMS-24). Results Students who show low adherence to the Mediterranean diet have a negative association with the repair of negative emotions. Participants who show a medium adherence to the Mediterranean diet, it is observed that they have a negative relationship with emotional clarity, while students who claim to have a high adherence to the Mediterranean diet show positive relationships with each of the constructs that make up emotional intelligence.